Being Nonreligious in Croatia: Managing Belonging and Non-Belonging - Hazdovac Bajić, Nikolina (Religions, 2022)
Catholicism in the Croatian context has been one of the most powerful sources of collective belonging for centuries. Since the fall of socialism, desecularization tendencies have manifested as homogenization, collectivization, and deprivatization of religion. (Non)religiosity became a contested issue, which not only implied belonging (ethnic, national, historical) but was also highly politicized. This paper aims to explore how living in a society with a dominant collective religion influences the experience of nonreligious people. The conducted research was based on 30 semi-structured interviews with people who self-identify as nonreligious, but at the same time are not members of nonreligious organizations. The obtained data show that some elements of collectivism can push individuals away from religion, but for some nonreligious people, religiosity remains an important identification framework. Keeping a connection with religion is achieved through conformist behaviors or "cherry-picking" elements of religiosity, which are then combined in individually-consistent worldviews. Nonreligious people sometimes feel "left out" and experience their nonreligiosity as lonely and isolating, which they often do not want to pass on to others. This creates a specific position for some nonreligious individuals that is simultaneously "in" and "out" of religion, and challenges the way nonreligiosity is often imagined.